Viaggi spirituali, itinerari culturali e cammini per lo sviluppo - Falqui, Enrico; Serenelli, Chiara (Ri-Vista. Research for landscape architecture, 2015)
The journey had played always a double function, in the literature’s imagination, meaning the goal and the final destination of the itinerary, but also the measure of distance from unknown realities and an impulse of searching new ideas and the Future. The outcoming Project of restoration an ancient route of pilgrimage from Rome to Loreto (Route Lauretana) is a new opportunity to create and increase the culture and the knowledge of the complex landscape and historical land’s systems whom are influenced in the ancient and in the modern age by the crossing Route of pilgrimage.